Transatlantic combined and comparative data analysis of 1095 patients with urea cycle disorders: a successful strategy for clinical research of rare diseases - Posset, Roland; Garbade, Sven; Boy, Nikolas; Hoffmann, Georg F.; Kölker, Stefan; Burgard, Peter (Journal of inherited metabolic disease, 2019)
Background To improve our understanding of urea cycle disorders (UCDs) prospectively followed by two North American (NA) and European (EU) patient cohorts. Aims Description of the NA and EU patient samples and investigation of the prospects of combined and comparative analyses for individuals with UCDs. Methods Retrieval and comparison of the data from 1095 individuals (NA: 620, EU: 475) from two electronic databases. Results The proportion of females with ornithine transcarbamylase deficiency (fOTC-D), particularly those being asymptomatic (asfOTC-D), was higher in the NA than in the EU sample. Exclusion of asfOTC-D resulted in similar distributions in both samples. The mean age at first symptoms was higher in NA than in EU patients with late onset (LO), but similar for those with early (≤ 28 days) onset (EO) of symptoms. Also, the mean age at diagnosis and diagnostic delay for EO and LO patients were similar in the NA and EU cohorts. In most patients (including fOTC-D), diagnosis was made after the onset of symptoms (59.9%) or by high-risk family screening (24.7%), and less often by newborn screening (8.9%) and prenatal testing (3.7%). Analysis of clinical phenotypes revealed that EO patients presented with more symptoms than LO individuals, but that numbers of symptoms correlated with plasma ammonium concentrations in EO patients only. Liver transplantation was reported for 90 NA and 25 EU patients. Conclusions Combined analysis of databases drawn from distinct populations opens the possibility to increase sample sizes for natural history questions, while comparative analysis utilizing differences in approach to treatment can evaluate therapeutic options and enhance long-term outcome studies.
Gesehen am 29.10.2019